Caregiver-related predictors of thermal burn injuries among Iranian children: a case-control study - Sadeghi-Bazargani, Homayoun; Mohammadi, Reza; Ayubi, Erfan; Almasi-Hashiani, Amir; Pakzad, Reza; Sullman, Mark J. M.; Safiri, Saeid (Public Library of Science (PLoS), 2017)
Purpose Burns are a common and preventable cause of injury in children. The aim of this study was to investigate child and caregiver characteristics which may predict childhood burn injuries among Iranian children and to examine whether confounding exists among these predictors. Methods A hospital based case-control study was conducted using 281 burn victims and 273 hospital-based controls, which were matched by age, gender and place of residence (rural/urban). The characteristics of the children and their caregivers were analyzed using crude and adjusted models to test whether these were predictors of childhood burn injuries. Results The age of the caregiver was significantly lower for burn victims than for the controls (P<0.05). Further, the amount of time the caregiver spent outdoors with the child and their economic status had a significant positive association with the odds of a burn injury (P<0.05). A multivariate logistic regression found that Type A behaviour among caregivers was independently associated with the child's odds of suffering a burn injury (OR = 1.12, 95% CI: 1.04–1.21). The research also found that children with ADHD (Inattentive subscale: Crude OR = 2.14, 95% CI: 1.16–3.95, Adjusted OR = 5.65, 95% CI: 2.53–12.61; Hyperactive subscale: Crude OR = 1.73, 95% CI: 1.23–2.41, Adjusted OR = 2.53, 95% CI: 1.65–3.87) also had increased odds of suffering a burn injury. However, several variables were identified as possible negative confounder variables, as the associations were stronger in the multivariate model than in the crude models.